Bilateral trade with a benevolent intermediary - Ran Eilat; Ady Pauzner (Theoretical Economics, 2021)
We study intermediaries who seek to maximize gains from trade in bilateral negotiations. Intermediaries are players: they cannot commit to act against their objective function and deny, in some cases, trade they believe to be beneficial. This impairs their ability to assist the parties relative to conventional mechanisms. We analyze this limited commitment environment as a standard mechanism design problem with an additional "credibility" constraint, requiring that every outcome be interim-optimal conditional on available information. We investigate how such intermediaries communicate with the parties, analyze the tradeoffs they face, and study the bounds on what they can achieve.
Keywords: C72; D82; D83; 330; Intermediation; mechanism design; imperfect commitment; asymmetric information; bilateral trade